Recent Advances in Herbal-Derived Products with Skin Anti-Aging Properties and Cosmetic Applications - Costa, Erika F. [UNESP]; Magalhães, Wagner V.; Di Stasi, Luiz C. [UNESP] (MDPI, 2022)
Although aesthetic benefits are a desirable effect of the treatment of skin aging, it is also important in controlling several skin diseases, mainly in aged people. The development of new dermocosmetics has rapidly increased due to consumers’ demand for non-invasive products with lower adverse effects than those currently available on the market. Natural compounds of plant origin and herbal-derived formulations have been popularized due to their various safe active products, which act through different mechanisms of action on several signaling pathways for skin aging. Based on this, the aim of the review was to identify the recent advances in herbal-derived product research, including herbal formulations and isolated compounds with skin anti-aging properties. The studies evaluated the biological effects of herbal-derived products in in vitro, ex vivo, and in vivo studies, highlighting the effects that were reported in clinical trials with available pharmacodynamics data that support their protective effects to treat, prevent, or control human skin aging. Thus, it was possible to identify that gallic and ferulic acids and herbal formulations containing Thymus vulgaris, Panax ginseng, Triticum aestivum, or Andrographis paniculata are the most promising natural products for the development of new dermocosmetics with skin anti-aging properties.
Keywords: cosmetic; herbal formulations; natural products; skin anti-aging